ICT skills of Library & Information Science (LIS) professionals for the adoption of Blended Learning: a case study of University of Colombo - Manatunga, P.K.S.; Silva, M.A.L. (University of Colombo, 2021)
Blended Learning (BL) is an emerging approach within the higher education sector in Sri Lanka. With the transformation, traditional work roles of LIS professionals arechanging, and challenges may arise due to lack of ICT skills. Based on the above assumption, the study sought to investigate the ICT skills of LIS professionals for the adoption of BL at the University of Colombo, with specific objectives; to identify the ICT skills required; the relationship between the ways of acquiring ICT skills and socio-demographic characters and ICT skillrelated factors affecting for BL. A survey research design was deployed using census. The data received were analyzed with descriptive statistics, correlation, and factor analysis using SPSS version 23. Reliability analysis was performed to measure the internal consistency of the questionnaire (α= 0.800). The majority (76.5%) of the LIS professionals use BL for knowledge sharing. All the respondents are competent in basic computer skills (Word Processing, PowerPoint) and novel technology skills (Google suit, Zoom), and acquire ICT skills by self-studying and web-based tutorials. Respondents need computers, laptops, the Internet, and Wi-Fi connection to acquire ICT Skills and reported that poor internet access affects the acquisition of ICT skills. Chi-Square test revealed that age and work experience showed a weak negative correlation with use of web-based tutorials (r=-0.486, p=0.028; r=-0.535, p=0.018 respectively) and obtaining information from peers (r=-0.314, p=0.009; r=-0.379, p=0.004respectively). Post hoc test revealed a significant association between acquiring information from peers with age group 51-60 years (p=0.0000)and 21-30 years of working experience (p=0.0001). Factor analysis revealed three main ICT related factors that affect BL; Digital readiness (α=0.850); attitude of students and policies (α=0.887), academic and humanistic standards of LIS professionals (α=0.886) and recommend to consider when adoptingBL.  The study concludes that LIS professionals are competent in ICT skills to adopt BL and recommend conducting training on programming languages, use of digital/interactive boards, and Tweeter. The current researchopens up opportunities for future research on BL.
Keywords: ICT skills; LIS Professionals; Blended Learning